Prediction of the Number of Arrivals of Training Students With the Monte Carlo Method - Sapriadi, Sopi; Yunus, Yuhandri; Dari, Rahmatia Wulan (Jurnal Informasi dan Teknologi, 2022)
The simulation of predicting student arrivals for training is an estimate of the calculation of the arrival rate of students in a period to conduct training. The number of student visits is too many, sometimes inversely proportional to the programmers who carry out learning, this causes the ongoing service to be less than optimal. This study aims to predict student arrivals in the future better. The data processed in this study were 3 periods sourced from the administration of a private company in West Sumatra. The data will be processed and calculated using the Monte Carlo method. The data were tested with various possible elements using a random sample. A powerful numerical calculation tool by simulating statistical data, this simulation obtains accurate values ​​​​accurately from the physical form of the system that can be observed. The calculation implementation will be developed using an application-based system that will be built with the Hypertext Preprocessor (PHP) programming language. The system developed is easier and more relevant by applying Information Technology. The results obtained in predicting are 80% for 2017 and 84% for 2018. From the results of 80% accuracy in 2017 and 84% 2018 the system works very well to implement. Based on the results of data processing with the Monte Carlo method, it can be predicted that the number of student arrivals for training, as well as a good and fast decision-making process in the future.